The Questions of Artistic Detachment and Tranquil Recollection in Iris Murdoch’s The Sea, the Sea - Barış Mete (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
Iris Murdoch’s 1978 novel The Sea, the Sea portrays an artist protagonist who mistakenly believes that it would be easy for him to detach from the glitter of life in London. After retiring from the theatre, the famous stage director and playwright Charles Arrowby decides to withdraw from what he has been accustomed to doing. He buys an old house in a coastal village where he thinks he will be able to recollect past emotions in tranquillity and write an autobiographical memoir. This is a clear reference to William Wordsworth’s particular idea of poetry. Yet, this becomes Charles’s most critical mistake as well, for life in the seaside village will bring him even more turbulence as he is away from the dazzling atmosphere of the theatre neither mentally nor bodily. His mind is always occupied with most of the names he has left behind in London. Besides, some of Charles’s old friends who are seeking a chance for revenge for his past misdeeds come to the village in order to blackmail and threaten him. As if his troubles are not enough, Charles meets his teenage love in the village, which turns him into an example of the ridiculous character of the Aristotelian theory of comedy and further spoils his supposed tranquillity. This study thus examines the notions of artistic detachment and tranquil recollection as two Wordsworthian concepts misconceived by Murdoch’s protagonist.